Cash, food, and vouchers reduce intimate partner violence in urban areas in Ecuador - Cash Transfer and Intimate Partner Violence Research Collaborative; London School of Hygiene and Tropical Medicine; UNICEF Office of Research-Innocenti (International Food Policy Research Institute, 2019)
This case study summarizes the impact of a short-term food, cash, and voucher program targeted to the urban poor in Northern Ecuador. The program led to a 30 percent reduction in physical and sexual IPV as well as a 19 percent reduction in controlling behaviors via decreases in marital conflict, increased family wellbeing, and women’s empowerment.